Vesiculobullous exanthema in a 3-month-old child with probable acute chikungunya infection - Farias, Luis Arthur Brasil Gadelha; Pires Neto, Roberto da Justa; Leite, Robério Dias (Journal of Health & Biological Sciences, 2019)
Objective: to report a rare case of a 3-month-old child with acute chikungunya infection presenting as vesiculobullous rash. Case description: herein we report a case of a 3-month-old infant which developed a diffuse erythematous rash involving the trunk and limbs within two days after sudden acute fever, and also presented striking irritability with inconsolable crying, hyporexia, cough, and coryza. Hematological and biochemical investigations were undertaken and were found to be normal. Serum samples were tested for Chikungunya revealing positive IgM. He was treated with supportive therapy, mainly with antipyretics, venous hydration and rest evolving with entirely resolution of the symptoms after four days. Comments: Chikungunya fever is a disease caused by the Chikungunya virus which can be found in endemic areas such as Brazil. Atypical manifestations can affect various systems including the skin and may be more frequent in children. The role of dermatological manifestations related to Chikungunya infection is not completely understood. The reported case is an unusual case of Chikungunya infection which highlights the importance of to know and to be aware of this manifestation in children mainly in new endemic areas such as Brazil.